2009
DOI: 10.1089/neu.2009-0956
|View full text |Cite
|
Sign up to set email alerts
|

Scaled cortical impact in immature swine: effect of age and gender on lesion volume

Abstract: The piglet scaled cortical impact model creates a focal contusion using a skull-mounted, spring-loaded blunt indentation device scaled to achieve identical tissue strains in subjects with different brain sizes. Preliminary data showed that contusion size increased proportional to subject age. This study details the results from a new, larger series of subjects of three ages, and compares the effect of age and additional host and physiologic variables on injury response. Sixty-seven subjects, including infant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…Furthermore, infant piglets had smaller lesions in response to scaled focal cortical impact than did toddler and adolescent piglets, but a greater total axonal lesion volume was observed at this same age compared with that in older piglets in response to angular deceleration. 17,18,58,64 Differences in study designs make it difficult to extrapolate the effect of trauma on humans with regard to neurogenesis and the ability to innately repair damaged tissue. Rates of neuronal migration under normal conditions in the human brain have yet to be determined, but we can expect, given the long distances involved, that it would take a long time for migrating neuroblasts to travel to a focal site of injury in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, infant piglets had smaller lesions in response to scaled focal cortical impact than did toddler and adolescent piglets, but a greater total axonal lesion volume was observed at this same age compared with that in older piglets in response to angular deceleration. 17,18,58,64 Differences in study designs make it difficult to extrapolate the effect of trauma on humans with regard to neurogenesis and the ability to innately repair damaged tissue. Rates of neuronal migration under normal conditions in the human brain have yet to be determined, but we can expect, given the long distances involved, that it would take a long time for migrating neuroblasts to travel to a focal site of injury in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although the response of the infant brain has been shown to be distinct from that of adolescents and adults, experimental studies that have focused on differences between the infant and toddler offer disparate evidence for the effect of maturation on injury response. Specifically, porcine focal lesion traumatic brain injury (TBI) models have demonstrated that geometricallyscaled cortical contusions produce smaller lesions at 1 week and 30 days post-injury in the infant than in the toddler (Duhaime et al, , 2003Missios et al, 2009), but that infant piglets may sustain larger decreases in cerebral blood flow (Armstead and Kurth, 1994) in the first 3 h following TBI than toddler piglets. Rodent models have shown that infant-age animals are more susceptible to apoptotic neurodegeneration in the initial 6-24 h immediately following mass-scaled weight drops (Bittigau et al, 1999), chronic cognitive deficits several weeks after injury , but similar white matter damage following contusive brain injury than toddler-age animals.…”
Section: Introductionmentioning
confidence: 99%
“…We used our wellcharacterized cortical impact model to induce mechanical trauma, as children with HH often have evidence of blunt mechanical trauma of some type. 6,22,23 Our cortical impact is reproducible and injures both gray and white matter. 24 We also induced mass effect, apnea, hypoventilation, and seizures to assess the role of these insults.…”
Section: Introductionmentioning
confidence: 89%
“…23,25 The brain was removed leaving the ventral dura intact and post-fixed at 4°C for up to 1 month. The eyes with attached optic nerves were removed by dissection through the floor of the anterior cranial fossa into the orbital space to expose the globe and contents of the orbit in a subset of injured piglets (n = 3).…”
Section: Protocol Specific To Experimental Phasementioning
confidence: 99%